2011
DOI: 10.1007/s10840-011-9630-9
|View full text |Cite
|
Sign up to set email alerts
|

Adverse response to cardiac resynchronisation therapy in patients with septal scar on cardiac MRI preventing a septal right ventricular lead position

Abstract: The presence of septal scar was associated with a poor acute and chronic response to CRT. This may relate to the inability to achieve a RV septal lead placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The potential relevance of RV pacing region scar was highlighted in a recent study by Duckett et al 24 that evaluated the feasibility of achieving a midseptal RV pacing position among 50 consecutive patients receiving CRT. In this study, a more conventional apical position was conceded to in those patients with poor R-wave pacing amplitudes (≤5 mV) and identified that these patients had a 67% prevalence of septal scar by LGE imaging versus 33% in those where adequate voltages were achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential relevance of RV pacing region scar was highlighted in a recent study by Duckett et al 24 that evaluated the feasibility of achieving a midseptal RV pacing position among 50 consecutive patients receiving CRT. In this study, a more conventional apical position was conceded to in those patients with poor R-wave pacing amplitudes (≤5 mV) and identified that these patients had a 67% prevalence of septal scar by LGE imaging versus 33% in those where adequate voltages were achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the concept of midseptal or RV outflow tract pacing has been shown to be both feasible [39][40][41][42] and potentially of clinical value. 24,42 In a study by Haghjoo et al, 40 patients otherwise receiving optimal LV pacing (ie, those with LV leads delivered to the posterolateral wall) had significantly higher CRT response rates when the RV lead was placed to the high (basal) septum compared with conventional apical placement (70% versus 30%; P=0.01). Furthermore, Duckett et al 24 showed that midseptal pacing was associated with improved response rate compared with apical pacing (70% versus 30%; P=0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,22,38 The most recently published study by Wong et al 22 showed that transmural scar was 3 times more prevalent in the RV versus LV pacing region, being seen in one-third of CRT patients. This study found that the delivery of both pacing leads to nonscarred regions resulted in an 82% response rate versus 55% if the RV pacing site was scarred, 25% if the LV site was scarred, and 0% if both were scarred.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the delivery of both pacing leads to nonscarred regions resulted in an 82% response rate versus 55% if the RV pacing site was scarred, 25% if the LV site was scarred, and 0% if both were scarred. While focused on basal RV septal lead placement, a small cohort study by Duckett et al 38 suggested that targeted placement of the RV lead to nonscarred basal septal segments was associated with greater response to CRT. This finding was in contrast to patients paced from a transmurally scarred RV apical segment who experienced a 36% absolute reduction in clinical response.…”
Section: Discussionmentioning
confidence: 99%